How do you evaluate sin^-1(sin((11pi)/10))?

2 Answers
Mar 29, 2018

Evalute the inner bracket first. See below.

Explanation:

sin(11*pi/10) = sin((10+1)pi/10 =sin(pi + pi/10)

Now use the identity:

sin(A+B) = sinAcosB +cosAsinB

I leave the nitty-gritty substitution for you to solve.

Mar 29, 2018

sin^-1(sin((11pi)/10))=-pi/10

Explanation:

Note:

color(red)((1)sin(pi+theta)=-sintheta

color(red)((2)sin^-1(-x)=-sin^-1x

color(red)((3)sin^-1(sintheta)=theta,where,theta in[-pi/2,pi/2]

WE have,

sin^-1(sin((11pi)/10))=sin^-1(sin((10pi+pi)/10))

=sin^-1(sin(pi+pi/10)).........toApply (1)

=sin^-1(-sin(pi/10))...........toApply(2)

=-sin^-1(sin(pi/10))..........toApply(3)

=-pi/10 in [-pi/2,pi/2]

Hence,

sin^-1(sin((11pi)/10))=-pi/10